Fundholding in general practice and financial risk. - Crump, B J (1991)
OBJECTIVE--To estimate the financial effect of random yearly variations in need for services on fundholding practices with various list sizes. DESIGN--A simulation model was derived using historical data on general practitioner referrals for the 113 surgical procedures covered by the general practitioner fund, combined with data on the hospital prices for those procedures. PATIENTS--Resident population of Central Birmingham Health Authority. MAIN OUTCOME MEASURES--Expected expenditure on the relevant surgical procedures for the whole district and for practices with list sizes of 9000, 12,000, 15,000, 18,000, 21,000, or 24,000 for each of 100 simulated years. RESULTS--By using average hospital prices for the West Midlands region the mean (SD) annual expenditure for the 179,400 residents was 4,832,471 pounds (87,149 pounds); the random variation between the 5th and 95th most expensive years was 5.7% of the mean cost. For a practice with a list size of 9000 the values were 244,891 pounds (18,349 pounds), with a variation of 27.5%. With a list size of 24,000 the values were 652,762 pounds (32,512 pounds), with a variation of 15.3%. CONCLUSIONS--Random variations in need for inpatient services will have a significant financial impact on the practice fund. The problem will be particularly great for smaller practices. Additional measures are required to ensure that the scheme is not undermined and that the potential benefits are secured.